Architecture from 'Résidences royales et impériales de France... - Auteur inconnu... (The British Library)
Notice issue d Europeana. This image has been taken from scan 000056 from "Residences royales et imperiales de France, histoire et monuments. [With plates.]". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
Droits : http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie; Iconographie